Vulnerability of Brazilian municipalities to hantavirus infections based on multi-criteria decision analysis. Issue 1 (December 2015) - Oliveira, Stefan; Fonseca, Lidsy; Araújo Vilges, Keline; Maniglia, Fernanda; Pereira, Simone; Caldas, Eduardo; Tauil, Pedro; Gurgel-Gonçalves, Rodrigo
Abstract Background Hantavirus infection is an emerging zoonosis transmitted by wild rodents. In Brazil, high case-fatality rates among humans infected with hantavirus are of serious concern to public health authorities. Appropriate preventive measures partly depend on reliable knowledge about the geographical distribution of this disease. Methods Incidence of hantavirus infections in Brazil (1993–2013) was analyzed. Epidemiological, socioeconomic, and demographic indicators were also used to classify cities' vulnerability to disease by means of multi-criteria decision analysis (MCDA). Results From 1993 to 2013, 1752 cases of hantavirus were registered in 16 Brazilian states. The highest incidence of hantavirus was observed in the states of Mato Grosso (0.57/100, 000) and Santa Catarina (0.13/100, 000). Based on MCDA analysis, municipalities in the southern, southeastern, and midwestern regions of Brazil can be classified as highly vulnerable. Most municipalities in northern and northeastern Brazil were classified as having low vulnerability to hantavirus cardiopulmonary syndrome. Conclusions Although most human infections by hantavirus registered in Brazil occurred in the southern region of the country, a greater vulnerability to hantavirus was found in the Brazilian Midwest. This result reflects the need to strengthen surveillance where the disease has thus far gone unreported.